Legislative Policy in Legalizing of Halal in Products Between Imitation and Justification "Animal Stoning and the Stable Life as a Case" - Ahmed Salem Ahmed Alejili (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
The Intermarry of halal with the trade and industry has led to the codify relationship between each other to produce a legitimate which is Halal products. But the attempts of halal industry's Legalization has been heavily influenced by the prevailing legal systems and led to the adopting various concepts that didn't meet the Halal principle, the very clear example that has chosen by the researcher to demonstrate and clarify that was the adoption of stoning process Before the slaughtering in halal standards, that contain many gaps in view of halal laws which led the researcher to highlight this problem to reconsider the halal standards legislative policy to become more conservative, and more inclined the towards of Islāmic law. by the analyzing of halal standards in the Islāmic Fiqh Academy and Malaysian standards and its adopting of Animal stoning the study has reached to the Infraction of stoning with the halal principle and lacking to any basis to prove the adoption of stoning to the halal consumers other than blind imitation and the effect of the carnivorous' food culture.